Comparison of Gas Assisted Hybrid EDM, Rotary EDM and Conventional EDM Processing of High Carbon High Chromium Die Steel - K. Singh, Nishant; Poras, Anand; Das, Subrato (International Journal of Engineering and Technology, 2018)
The high carbon high chromium die steel is most widely used in various industrial applications. However, effective machining of high carbon-chromium die steel is extremely difficult due to its high hardness and stiffness. In the present work, comparative analysis of Gas Assisted Hybrid EDM (GAHEDM), Rotary EDM (REDM), and Conventional EDM processes have been done with respect to process responses like electrode wear ratio (EWR), material removal rate (MRR), and surface roughness (SR). Experimentation has been done to the study influence of process factors like discharge current, pulse on time, duty cycle, tool rotation and discharge gas pressure on MRR, EWR and SR. Further, from a comparative study, it has been observed that high MRR, low EWR and low SR are obtained in GAHEDM process in comparison of REDM and EDM processes. Analysis of surface morphology reveals that the formation of recast layer and cracks on the surface are fewer in number on work piece machined by GAHEDM process with respect to specimen machined with REDM and EDM processes. The results show that the use of compressed helium gas in GHEDM process has a positive impact on the machining performance. This process may be used for industrial machining operation.Â Â